ChemInform Abstract: Catalytic Asymmetric Synthesis of Substituted Morpholines and Piperazines. Issue 21 (2nd May 2013) - Zhai, Huimin; Borzenko, Andrey; Lau, Ying Yin; Ahn, Shin Hye; Schafer, Laurel L.
Abstract Strategies are detailed for the preparation of 3‐substituted morpholines and 2, 5‐disubstituted piperazines involving a hydroamination with N, O‐chelated Ti catalyst as key step.